Improvement of coal boiler's efficiency after application of liquid fuel additive. (October 2020) - Junga, Robert; Pospolita, Janusz; Niemiec, Patrycja; Dudek, Maciej; Szleper, Rafał
Highlights: Complex research of the fuel additive with the use of TGA/DSC and two coal boilers. Additive changes the characteristic parameters of coal. Application of the additive decreases oxygen concentration. Efficiency of low power boiler increased by 2.49 percentage point. Efficiency of industrial power boiler increased by 2 percentage point. Abstract: The aim of research is to provide a comprehensive view of the combustion process of coal with a liquid fuel additive. The studies were carried out in laboratory conditions and on low and high power boilers which are usually used in households and local district heating plants. TGA/DSC analysis shows that the additive decreases the ignition temperature of coal as well as increases the maximal heat flow and its temperature. Application of the additive significantly decreases oxygen O2 concentration, while maintaining the same flue gas temperature. This affects the increase of efficiency of low power boiler by 2.49 p.p. (percentage point). Emission of hydrocarbons, formaldehyde, benzene and hydrogen cyanide was lowered, whereas there was no significant impact on SO2 and NOx emission. The studies carried on the industrial boiler with thermal output of 12 MW demonstrate that the flue gas heat loss and unburnt fuel heat loss decreased by ca. 2 p.p. As a result, the efficiency increased from ca. 86 to 88% which, in turn, influences the decrease of CO2 emission per unit of energy by 5%. The originality of the work is comprehensive research on the impact of additive on the coal combustion process, mainly concerning the efficiency.